Innovative Uses of Rain Screen Cladding. CFD and Gas Dispersion Analysis of a Prototype. (December 2015) - Albo, A.; Cumo, F.; Frullini, M.; Giustini, F.
Abstract: In this work, both CFD and CH4 dispersion analysis in rain screen cladding were carried out, in order to reduce the visual impact of Natural Gas distribution network in civil buildings ensuring high safety standards. In the first part of the work it was conducted the parametric analysis in order to identify the main physical parameters that influence the air velocity in air-gap. Subsequently, CFD simulations were carried out in order to evaluate how the geometric and constructive characteristics can influence the air velocity inside the cavity. In particular, were realized both 2D and 3D models, and was used Ansys Fluent 6.3 software. Finally, Natural Gas dispersion analysis was carried out, in order to evaluate the safety against explosive atmosphere.